Diversity of immune checkpoints in cancer immunotherapy - Guo, Zhangyan; Zhang, Rui; Yang, An-Gang; Zheng, Guoxu (Frontiers in Immunology, 2023)
Finding effective treatments for cancer remains a challenge. Recent studies have found that the mechanisms of tumor evasion are becoming increasingly diverse, including abnormal expression of immune checkpoint molecules on different immune cells, in particular T cells, natural killer cells, macrophages and others. In this review, we discuss the checkpoint molecules with enhanced expression on these lymphocytes and their consequences on immune effector functions. Dissecting the diverse roles of immune checkpoints in different immune cells is crucial for a full understanding of immunotherapy using checkpoint inhibitors.